TO A PROBLEM OF CREATION OF GEOINFORMATION HYDRO-GEOLOGICAL MODELS - MOKIIENKO, V.; KOSHLIAKOV, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The approach to creation of geoinformation hydro-geological model on a basis of hydro-geological determined model is stated. At creation of geoinformation hydro-geological model the geoinformation systems MapInfo and ArcView are used. Object of research is the underground water flow on the left coast in Kiev city.